A 'post-liberal peace' via Ubuntu?. (2nd January 2018) - Tom, Patrick
ABSTRACT: A number of scholars concur that contemporary peace support operations have largely drawn on the 'liberal peace' paradigm. Recent critical critiques on the liberal peace have noted that although international interventions have used the liberal peace model as a 'blue print', 'post-conflict spaces' follow their own logic, and local actors have expressed agency in their interaction with international actors and the liberal peace. Some of the critiques, notably Oliver Richmond and Roger Mac Ginty, have suggested the need to engage in empirical research that investigates the liberal-'local' interface in post-war societies and the hybrid forms of peace it produces. Drawing on this critique and literature on ubuntu, this article attempts to open up a discussion on how ubuntu and post-conflict societies that subscribe to the philosophy and practice of ubuntu are interacting with the (neo)liberal peace, and the liberal state and its institutions, and the forms of peace that are being produced.